Strategi Penerapan Kebijakan Sovereign Wealth Funds (SWFs) di Indonesia: Studi Literatur dan Studi Komparatif Oman - Eko Eddya Supriyanto (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
The application of Sovereign Wealth Funds (SWFs) in monetary policy is a solution to the counter-globalist policies that have so far prevented developing countries from being able to move into developed countries. The State of Oman is an inspiration for the kingdom of Saudi Arabia in the policy of Sovereign Wealth Funds (SWFs) which change the direction of state policy on hospitality services for pilgrims Umroh and Hajj. The oman state also has been a country that focuses its main income on petroleum to calculate all its petroleum assets which are then sold in the form of Sovereign Wealth Funds (SWFs) to change the country's policy on tourism hospitality activities. This research will explain SWFs in terms of definition, history and concept, then we will see the application of SWFs in oman countries that have been going on since 2010. The implementation strategy of SWFs in Indonesia certainly requires courage from the Indonesian government because the presence of rare mineral content in this country is certainly very needed for high-tech materials in developed countries in the world. Indonesia is very likely to implement SWFs and can become developed countries with a model of applying SWFs on rare earth minerals owned by Indonesia, which are entirely in this country.